APPLICATION OF THE RIGHT TO EDUCATION IN CHILDREN'S CORRECTIONAL INSTITUTIONS TO PRISONERS - Manuputty, Alma; Tudor, Megan E. (SYNTIFIC, 2024)
Background. Development of correctional students in juvenile correctional institutions consistent with the Minister of Justice's Decree No. M.02-PK.04.10 of 1990 Governing Patterns of Development for Prisoners/Detainees, the training pattern for inmates serves as a guide. The purpose of this study was to examine the legislation about the dismissal of inmates and the implementation of the right to education for them, as outlined in Law Number 12 of 1995 about Corrections. Research Method. The research method used a normative juridical approach. This research analyzed systematically, methodologically, and consistently in the future. Through this research process, research was carried out analysis and construction of data were collected and processed. Findings. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System states that for children, the threat of criminal punishment for offenses is halved; that is, an offense carrying an eight-year prison sentence will only be threatened with four years in prison, and they will be placed under detention conditions (threat of five years or more). Out of all the rights mentioned above, the right to instruction and education is the one that has the strongest connection to children's mental development. It was previously said that although improving the nation's intelligence is one of the state's goals, children with legal issues do not receive the education they need. Conclusion. In correctional facilities, children should prioritize their rights, including education, over their obligations, as denying this right can lead to ignorance and hinder the well-being of the child.